PENGARUH PEMBIAYAAN PERBANKAN TERHADAP KINERJA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI INDONESIA - Farah Chalisa; Muhammad Maulana; Israk Ahmadsyah (JIM : Journal Of International Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a fundamental pillar of Indonesia’s economy, contributing significantly to employment generation and income distribution. However, limited access to formal financing remains a key obstacle to improving MSME performance and expanding business capacity. This study aims to examine the effect of bank financing on MSME performance in Indonesia, measured by production value, assets, and employment. This research uses provincial-level panel data of MSMEs in Indonesia from 2017 to 2023, excluding several newly established provinces. Panel data regression analysis is applied to investigate the impact of investment financing and working capital financing on MSME performance indicators. The findings reveal that bank financing has a positive and significant effect on production value, asset growth, and labor absorption. These results underline the strategic role of banks as financial intermediaries in supporting MSME development and promoting sustainable and inclusive economic growth in Indonesia.